2020
DOI: 10.1111/imm.13258
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 4 deficiency in CD8+ T cells abrogates terminal effector differentiation and promotes transplant acceptance

Abstract: Allogeneic CD8 + cytotoxic T cells play an essential role in rejecting transplanted allografts, but how their effector function is regulated on a transcriptional level remains unclear. Herein, we investigate the role of interferon regulatory factor 4 (IRF4) in controlling CD8 + T-cell function in response to transplant. B6.Rag1 À/À mice were adoptively transferred with CD8 + T cells isolated from either Irf4 fl/fl Cd4-Cre (T-cell-specific Irf4deficient) or Irf4 fl/fl control mice, followed by BALB/c skin trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In the laboratory settings, WT B6 recipients reject the minor histocompatibility antigen-mismatched heart allografts, but CD8 + T cell-deficient recipients fail to do so ( 5 ). Moreover, we and others have demonstrated previously that lymphopenic mice reconstituted with CD8 + T cells alone acutely reject MHC fully mismatched allografts ( 6 , 7 ), suggesting that the adoptively transferred CD8 + T cells differentiate into cytotoxic effector T cells and sequentially drive the rejection of allografts in these lymphopenic recipients ( 7 ).…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…In the laboratory settings, WT B6 recipients reject the minor histocompatibility antigen-mismatched heart allografts, but CD8 + T cell-deficient recipients fail to do so ( 5 ). Moreover, we and others have demonstrated previously that lymphopenic mice reconstituted with CD8 + T cells alone acutely reject MHC fully mismatched allografts ( 6 , 7 ), suggesting that the adoptively transferred CD8 + T cells differentiate into cytotoxic effector T cells and sequentially drive the rejection of allografts in these lymphopenic recipients ( 7 ).…”
Section: Introductionmentioning
confidence: 64%
“…Recent studies have found that BATF and IRF4 cooperate to directly bind to and regulate gene expressions in T cells, such as Tcf7 and Tbx21 (encoding TCF1 and T-bet, respectively) ( 24 , 55 ). Of note, we have found previously that the deletion of IRF4 in T cells promotes transplant acceptance ( 21 ), and that IRF4-deficient CD8 + T cells fail to differentiate into effectors upon transfer into immunocompromised recipients ( 7 ). The cooperation between BATF and IRF4 appears to be essential in allogeneic T cell fate decisions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations